Analyzing Porter’s Competitive Forces for Enterprise Success: A case study of the South Mills Corporation - Umash - Biskra - Chenafi, Nawal (Journal of Human Sciences, 2022)
The study examined the competitive strengths of Porter at the Greater Mills-South-Omach-Biskra Foundation. The aim of the study was to determine the extent of the organization’s interest in analyzing its competitive environment. The questionnaire was used as a basic tool for data collection. It was distributed to the study community through a comprehensive survey of its 35 frames, The number of valid questionnaires was 30 analysis to be analyzed using the 19 spssv statistical program. The study concluded that there is an interest of the institution in analyzing its competitive forces, especially that its interest is more evident in the current competitors. Therefore, this study recommended that the organization should be aware of all developments in its surrounding environment to achieve excellence and competitive advantage.